Análise das propriedades mecânicas, grau de conversão e profundidade de polimerização de resinas compostas polimerizadas com diferentes unidades fotoativadoras de LED - Almeida, Laís da Mata (2021)
This study analyzed the irradiance and spectrum by emission spectrophotometry (MARC-RC), characterized the light beams (Beam Profile), as well as determined the Knoop microhardness (KHN), the modulus of elasticity (GPa), the degree of conversion ( %), the flexural strength of 3 points (MPa) and the polymerization depth with elasticity modulus of a composite (Filtek Z350 XT) photopolymerized with 5 different types of LED curing units. Of these, three types were not certified by ANVISA and Inmetro, Dental Wireless (E1), Li A180 (E2) and Lyang Ya (E3), and two with certification, VALO Cordless - Ultradent (VL) and Elipar Deep-Cure L - 3 Oral Care (EL). The characterization was carried out by determining irradiance (mW / cm²), emission spectrum (mW / cm² / nm) and radiant exposure (J / cm²) using the MARC Resin Calibrator (MARC-RC, BlueLight). The Beam Profile of the different photoactivating units was made by means of a laser beam profile reader (Beam Profile). 50 specimens were produced for testing microhardness and modulus of elasticity. Each experimental group was polymerized with a photoactivator unit. Microhardness (KHN) was obtained by averaging five indentations on each surface. The modulus of elasticity was obtained by measuring the major and minor diagonals of each indentation. The degree of conversion was obtained by the FTIR / ATR test with 25 specimens. The 3-point flexural strength test (n = 50) was performed using a load in the center of the sample with a constant speed of 0.5 mm / min until fracture. The maximum load was recorded in Newtons. The depth of polymerization of the restoration was evaluated by Knoop microhardness using the average indentations in the regions: mesial, center and distal of healthy human molars prepared in Class II and restored using an oblique incremental technique. The modulus of elasticity of the polymerization depth of the restoration was obtained in the same way as the previous microhardness test. The test data were subjected to the normality test (Shapiro-wilk) followed by Factor analysis of variance (One-way ANOVA), Two-factor analysis of variance (Two-way ANOVA), Tukey HSD test (α = 0, 05) and multiple linear regression. In all tests, the groups showed statistically significant differences between them (p <0.001). The non-certified units (E1, E2 and E3) presented nonhomogeneous light beam profiles with concentrated irradiance in the center of the active tips. E3 showed greater irradiance when compared to the other photoactivating units. VL and EL showed larger diameters between the different photoactivating units. In the microhardness (KHN) and elastic modulus (GPa) tests, VL presented the highest mean values in both and E1, the lowest mean values. VL showed higher values of degree of conversion (%) when compared to EL and E3. The highest values of flexural strength (MPa) were E3 when compared to the other groups, being statistically similar to the VL and E2 groups. At depths closer to the pulp wall, lower mean values of microhardness and modulus of elasticity were obtained. And, the highest mean values of microhardness and modulus of elasticity were found in the occlusal regions (1mm). The interaction between microhardness and modulus of elasticity showed a very strong and proportional positive correlation according to the different depths tested. The analysis of the tests indicated that between microhardness (KHN) and depth of the restoration, a weak positive correlation was obtained and there was no association with irradiance (mW / cm²). The modulus of elasticity (GPa) was not related to the depth of the restoration and to the irradiance (mW / cm²).